Pelatihan Dasar-Dasar Kewirausahaan pada Mini Project Sains terhadap Anak-Anak Jalanan Kota Makassar - Arif, Rifda Nur Hikmahwati; H. Muhiddin, Nurhayani; Fauziatul, Noor; Ahmad, Fandi; Damayanti, Putri (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
The purpose of this community service is to help street children in the city of Makassar acquire productive skills through basic entrepreneurship training. The community service activities are carried out at the Science Education Study Program, FMIPA UNM. The method of implementing community service activities for basic entrepreneurship training for street children in the city of Makassar is conducted. The result of the community service activities is the creation of productive skills in entrepreneurship both before and after the training. It is hoped that this community service will help children improve their production skills, especially in helping them become better entrepreneurs.